(untitled) (Journal of Architectural Design, 2022)
The rich architectural traditions of Uzbekistan embody all stages of the development of the world cultural heritage, and various forms of rare architectural works, and have left a significant mark on the architecture of unique structures such as towers. The article discusses the skilful work of the skilled master architect from Andijan in the construction of baths and the students he trained.